1964
DOI: 10.1177/030098586400100103
|View full text |Cite
|
Sign up to set email alerts
|

The Pathology of Abortion Caused by the Virus of Infectious Bovine Rhinotracheitis

Abstract: The original reports of infection by the virus of infectious bovine rhinotracheitis (IBR) emphasized the respiratory nature of the disease it produced (7). Subsequent investigations have indicated its pleomorphic character, first with the recognition of a venereal form (6 , 8 , IO), later a conjunctival type of infection (I, 9) and most recently the observations of a phase of the infection characterized by encephalitis (2, 4, 5). Serological studies and field observations have indicated that infection by this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

1973
1973
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 3 publications
1
16
0
1
Order By: Relevance
“…In North America the ability of both wild type field strains and early modified live vaccines to induce abortion has been recognised with one of the earliest reports from 1964 [28] describing the pathology of abortions due to BoHV-1 from a naturally occurring outbreak, experimental studies and following use of modified live vaccine in pregnant cattle. This study suggested an age-related susceptibility of the foetus with almost all abortions occurring in cows pregnant for at least six months.…”
Section: Reviewmentioning
confidence: 99%
“…In North America the ability of both wild type field strains and early modified live vaccines to induce abortion has been recognised with one of the earliest reports from 1964 [28] describing the pathology of abortions due to BoHV-1 from a naturally occurring outbreak, experimental studies and following use of modified live vaccine in pregnant cattle. This study suggested an age-related susceptibility of the foetus with almost all abortions occurring in cows pregnant for at least six months.…”
Section: Reviewmentioning
confidence: 99%
“…There is substantial evidence that the fetus may become infected after the pregnant cow has been inoculated with a vaccine containing the live virus of IBR (52,58,60,82) or Rift Valley fever (RVF) (15,95). Although it was concluded from early studies that chick embryo-adapted (31) and lapinized (7) rinderpest viral vaccines were safe for use in pregnant cows, more recent data indicate that pregnant cows of some especially susceptible stock aborted after receiving lapinized vaccine (86).…”
Section: Wt Ttv~bert Et Almentioning
confidence: 99%
“…Abortions occur following clinical or subclinical IBRV infection in pregnant cows (36,41,108,124,142,227,228) or following vaccination with intramuscular IBRV vaccines (see intramuscular MLV vaccines). Abortions associated with natural disease outbreaks have been restricted until recently to the North American continent (56,112,245).…”
Section: Abortionmentioning
confidence: 99%
“…Virus was consis tently isolated from placenta and cotyledons following IBRV induced abortion (118,122,191), Infected placentomes obtained by cesarean section (121) or less than 24 hours after fetal death (122) were normal on histological examination. Severe edema and necrosis of the placenta observed 24 hours after fetal death were nonspecific changes caused by fe^^l death (121,122,176,191), viremia in the fetus caused multifocal coagulative necrosis of liver and spleen (118,122,124,191,278) and intravaginal (180). Neural lesions included leptomeningitis, encephalomyelitis, perivascular cuffing, focal gliosis and sensory ganglionitis (8,11,72,178,179,180).…”
Section: Abortionmentioning
confidence: 99%